The Wordplay μαθεῖν-παθεῖν in Hebrews 5:8 - Dyer, Bryan (2021)
Abstract This article examines the use and history of the wordplay μαθεῖν-παθεῖν in Greco-Roman literature in order to assess its use in the Epistle to the Hebrews. First, two important studies on the wordplay from the mid-twentieth century are examined in addition to recent Hebrews scholarship. Second, the article surveys Greco-Roman literature, including several texts not previously included in previous scholarship, to explore how this wordplay was used and developed. Finally, the use of μαθεῖν-παθεῖν in Heb 5:8 is investigated in light of its prior use in Greek literature. It is argued that in these two words, the author of Hebrews is able to memorably demonstrate that Jesus participated in the full human condition. This supports the larger argument regarding Jesus’ qualifications for the high priesthood and is put in conversation with his status as the divine Son.
Keywords: Human Nature; Jesus Christ; Christology; Greco-Roman literature; Hebrews